Role of Village Head Leadership in Realizing Good Governance (A Qualitative Descriptive Research in Sigalapang Julu Village, Panyabungan District, Mandailing Natal Regency) - Zainal Arifin Daulay (The International Journal of Politics and Sociology Research, 2022)
This study tries to describe the facts about the Leadership Role of the Village Head in realizing Good Governance in Sigalapang Julu Village in 2011. The theory used to describe this problem is the theory of Good Governance, which is a method and concepts about the implementation of good governance. Good Governance is the main foundation in running a democratic and good government, especially in village government. This thesis also looks at the leadership role of the Village Head in carrying out the concepts of Good Governance in running village government, so that good government can be realized. And how the Village Head can implement a policy and service to the village community. In this study using a qualitative descriptive method, namely research that is used to describe the atmosphere that occurs in the field based on observed data, behavior, speech, and writing. The interview method was used as the main technique of data collection. Data were analyzed through interviews through their relevance to the theory used.